Golimumab Ameliorates Pancreatic Inflammatory Response in the Cerulein-Induced Acute Pancreatitis in Rats - Mustafa Kaplan,; Alpaslan Tanoğlu,; Başak Çakır Güney,; Murat Yeniçeri,; Zafer Çırak,; Yeşim Önal Taştan,; Ayşe Gökçen Sade, (Turkish Journal of Gastroenterology, 2022)
Background: The aim of the study was to evaluate whether a new and successful treatment opportunity can be provided in acute pancreatitis and may prevent symptomatic treatments and show its effect through etiopathogenesis. Therefore, we want to investigate the efficacy of golimumab in an experimental rat model of cerulein-induced acute pancreatitis.Methods: A total of 35 rats, including 7 rats in each group, were distributed into 5 groups (sham, acute pancreatitis, placebo, acute pancreatitis+golimumab 5 mg/kg, and acute pancreatitis+golimumab 10 mg/kg). An experimental cerulein-induced acute pancreatitis model was accomplished by intraperitoneal cerulein injections. After sacrification, rat blood samples were collected for amylase, IL-6, and IL-1beta measurements. Histopathological analysis of the pancreas was performed with Tunel and hematoxylin & eosin staining.Results: Amylase, IL-6, and IL-1beta levels were found to be increased in the acute pancreatitis group. IL-1beta, amylase, IL-6 levels, and pancreatic inflammation were all significantly decreased in golimumab groups (P < .01). Moreover, in both golimumab groups, golimumab treatment significantly reduced apoptosis in pancreatic tissues (P < .05). Golimumab treatment was found to significantly reduce edema formation, inflammation, vacuolization, and fat necrosis of pancreatic tissues (P < .05).Conclusion: Firstly in the literature, we investigated the efficacy of golimumab in the experimental acute pancreatitis model. In the light of our findings, it could be suggested that golimumab may be an effective and safe therapeutic option in the treatment of patients with acute pancreatitisCite this article as: Kaplan M, Tanoğlu A, Çakır Güney B, et al. Golimumab ameliorates pancreatic inflammatory response in the cerulein-induced acute pancreatitis in rats. Turk J Gastroenterol. 2022;33(11):918-924.